Overexpression of GmFDL19 enhances tolerance to drought and salt stresses in soybean. - Yuanyuan Li; Quanzhen Chen; Haiyang Nan; Xiaoming Li; Sijia Lu; Xiaohui Zhao; Baohui Liu; Changhong Guo; Fanjiang Kong; Dong Cao (PLoS ONE)
The basic leucine zipper (bZIP) family of transcription factors plays an important role in the growth and developmental process as well as responds to various abiotic stresses, such as drought and high salinity. Our previous work identified GmFDL19, a bZIP transcription factor, as a flowering promoter in soybean, and the overexpression of GmFDL19 caused early flowering in transgenic soybean plants. Here, we report that GmFDL19 also enhances tolerance to drought and salt stress in soybean. GmFDL19 was determined to be a group A member, and its transcription expression was highly induced by abscisic acid (ABA), polyethylene glycol (PEG 6000) and high salt stresses. Overexpression of GmFDL19 in soybean enhanced drought and salt tolerance at the seedling stage. The relative plant height (RPH) and relative shoot dry weight (RSDW) of transgenic plants were significantly higher than those of the WT after PEG and salt treatments. In addition, the germination rate and plant height of the transgenic soybean were also significantly higher than that of WT plants after various salt treatments. Furthermore, we also found that GmFDL19 could reduce the accumulation of Na+ ion content and up-regulate the expression of several ABA/stress-responsive genes in transgenic soybean. We also found that GmFDL19 overexpression increased the activities of several antioxidative enzyme and chlorophyll content but reduced malondialdehyde content. These results suggested that GmFDL19 is involved in soybean abiotic stress responses and has potential utilization to improve multiple stress tolerance in transgenic soybean.